Usefulness of Heart Rate to Predict One-Year Mortality in Patients With Atrial Fibrillation and Acute Myocardial Infarction (from the OMEGA Trial) - Li, Jin; Becker, Rüdiger; Katus, Hugo (The American journal of cardiology, 2013)
In the setting of acute myocardial infarction and sinus rhythm, the heart rate (HR) has been demonstrated to correlate closely with mortality. In patients presenting with acute myocardial infarction and atrial fibrillation (AF) on admission, however, the prognostic relevance of the HR has not yet been systematically addressed. A post hoc subgroup analysis of the data from the OMEGA trial was conducted to analyze whether the admission HR determines the 1-year mortality in patients presenting with AF in the setting of acute myocardial infarction. Of 3,851 patients enrolled in the OMEGA study, 211 (6%) presented with AF on admission. This subgroup was dichotomized according to the admission HR (cutoff 95 beats/min). Multiple regression analysis revealed that an admission HR of ≥95 beats/min independently determined the 1-year mortality in patients with AF (odds ratio 4.69, 95% confidence interval 1.47 to 15.01; p = 0.01). In conclusion, this is the first study demonstrating that a high HR (≥95 beats/min) on admission in patients with AF and acute myocardial infarction is associated with an almost fivefold mortality risk.